2007
DOI: 10.1042/bst0350356
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-based analogues as biochemical probes and potential therapeutics

Abstract: The polyamines putrescine, spermidine and spermine are ubiquitous polycationic compounds that are found in nearly every cell type, and are required to support a wide variety of cellular functions. The existence of multiple cellular effector sites for naturally occurring polyamines implies that there are numerous targets for polyamine-based therapeutic agents. Through a programme aimed at the synthesis and evaluation of biologically active polyamine analogues, our laboratory has identified three distinct struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Although inhibitors of virtually all of the biosynthetic enzymes in polyamine metabolism have been synthesized, none has demonstrated clinical efficacy as a single agent in clinical trails for cancer (see [20]). In an attempt to overcome the limitations encountered with specific inhibitors of enzyme function, we and others have exploited the self-regulatory properties of polyamine metabolism for therapeutic advantage through the use of structural analogues of the natural polyamines [4,5,8,18,39,43,44,49]. The initial studies with polyamine analogues, particularly with BENSpm, were promising, but clinical trials with a number of analogues in lung, breast, and other tumors did not reveal efficacy as single agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibitors of virtually all of the biosynthetic enzymes in polyamine metabolism have been synthesized, none has demonstrated clinical efficacy as a single agent in clinical trails for cancer (see [20]). In an attempt to overcome the limitations encountered with specific inhibitors of enzyme function, we and others have exploited the self-regulatory properties of polyamine metabolism for therapeutic advantage through the use of structural analogues of the natural polyamines [4,5,8,18,39,43,44,49]. The initial studies with polyamine analogues, particularly with BENSpm, were promising, but clinical trials with a number of analogues in lung, breast, and other tumors did not reveal efficacy as single agents.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these inhibitors have not proven useful for cancer therapy, since the compensatory increase in the target enzymes and polyamine uptake in response to a drop in polyamine content overcomes their antiproliferative effects. Induction of SSAT by polyamine analogs provides an alternative approach that is undergoing trials, and combination therapy may be valuable (12,16,25,133). Although it has been suggested that SSAT may be a useful target for many other diseases based on the plethora of effects of SSAT described in this review, it is obvious that such therapeutic intervention must be very carefully designed to avoid unwanted side effects due to alterations in nontarget cells.…”
Section: Summary and Future Directionsmentioning
confidence: 97%
“…A wide variety of polyamine analogs has been examined for use as cancer chemotherapeutic drugs, and some of the many promising results seen in laboratory experiments have been moved forward into clinical trials (14,16,24,25,56). Early studies with some analogs such as BE-3-3-3 showed that they produced a massive induction of SSAT and decline of polyamines in sensitive tumors, and it was postulated that their antitumor action was due to polyamine depletion mediated via both SSAT induction and repression of the polyamine biosynthetic enzymes.…”
Section: Induction Of Ssatmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, disturbed cellular functions and cytotoxicity may result. The development of polyamine-based molecules for therapeutic purposes is an ongoing field of research and, for example, the N-terminally alkylated polyamine analogue DENSpm ( N 1 , N 11 -diethylnorspermine) has been in clinical trials as an agent against several human solid tumours [4,5]. Antiproliferative action of DENSpm seems, at least in some cell lines, to be connected to the induction of SSAT [6–8].…”
Section: Introductionmentioning
confidence: 99%